Peningkatan Kemampuan Mengenal Nilai Mata Uang Melalui Metode Bermain Peran pada Anak GSA Kelas VI SLB Negeri Tanjungpandan Belitung - Perawati, Rika; Ardisal , Ardisal; Rahmahtrisilvia, Rahmahtrisilvia; Mahdi, Arisul; Muspita, Rila (Indo-MathEdu Intellectuals Journal, 2026)
Children with mild autism have difficulty understanding the abstract concept of currency value, so they need concrete learning media to develop their independence in daily activities. This study aims to improve the understanding of the concept of currency value in mild autistic children in Grade IV at a special school. The study uses a descriptive qualitative approach with a classroom action research (CAR) design. The research subjects were children with mild autism in the fourth grade of SDLB, with the class teacher as a source of supporting data. Data collection techniques included observation, interviews, documentation, currency value concept comprehension tests, and instrument validation. Data analysis techniques were carried out qualitatively through data reduction, data presentation, and conclusion drawing, supported by test result analysis to see the increase in concept comprehension. The results showed that the role-playing method could improve mildly autistic children's understanding of currency values, as indicated by increased test scores and increased active participation of children in learning. Through role-playing activities, children could more easily understand the function of money in daily life through simulated buying and selling and contextual activities in the classroom. Thus, the role-playing method was declared effective in teaching mildly autistic children about currency values.